La soberanía del ciberespacio : algunas reflexiones sobre el concepto de Estado, soberanía y jurisdicción frente a la problemática que presenta internet - Rabinad, María Gimena (2008)
The author mentions the effects of the expansion of the Internet with respect to the traditional conception of the state and analyzes its positive and negative consequences in light of different theories. Hence, she finds a mutation in the concept of sovereignty, which leans to the logic of the Empire, featured by an absence of fix barriers or frontiers. Finally, she examines the conflicts being faced by states as a consequence of this transformation and the solutions that have been proposed